Making policy public : participatory bureaucracy in American democracy - Moffitt, Susan L. (Cambridge : Cambridge University Press, 2014)
This book challenges the conventional wisdom that government bureaucrats inevitably seek secrecy and demonstrates how and when participatory bureaucracy manages the enduring tension between bureaucratic administration and democratic accountability. Looking closely at federal level public participation in pharmaceutical regulation and educational assessments within the context of the vast system of American federal advisory committees, this book demonstrates that participatory bureaucracy supports bureaucratic administration in ways consistent with democratic accountability when it focuses on complex tasks and engages diverse expertise. In these conditions, public participation can help produce better policy outcomes, such as safer prescription drugs. Instead of bureaucracy's opposite or alternative, public participation can work as its complement.
1. Portals of democracy in American bureaucracy -- 2. Participatory bureaucracy in practice -- 3. The Development of Public Committees -- 4. Making educational performance public: reporting on the progress of education -- 5. Private knowledge for public problems: regulating pharmaceutical information -- 6. Setting the public agenda -- 7. Deliberate participation -- 8. The impact of public advice -- 9. Participatory bureaucracy in American democracy.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Political planning -- United States; Bureaucracy -- United States; Administrative agencies -- United States; Citizens' advisory committees -- United States; Government accountability -- United States; Transparency in government -- United States; Education and state -- United States; Pharmaceutical policy -- United States